Neuromonitoring Using Motor and Somatosensory Evoked Potentials in Aortic Surgery. Issue 6 (19th May 2016) - Liu, Lucy Y.; Callahan, Brooke; Peterss, Sven; Dumfarth, Julia; Tranquilli, Maryann; Ziganshin, Bulat A.; Elefteriades, John A.
Abstract: Background: Motor evoked potentials (MEP) and somatosensory evoked potentials (SSEP) are established methods of neuromonitoring aimed at preventing paraplegia after descending or thoracoabdominal aortic repair. However, their predictive impact remains controversial. The aim of this study was to evaluate our single‐center experience using this monitoring technique. Methods: Between 2009 and 2014, 78 patients (mean age 66 ± 12, 53% male) underwent either descending or thoracoabdominal aortic repairs. Of these, 60% had an aortic aneurysm, 30% dissection, and 10% other etiologies. Intraoperatively, MEPs and SSEPs were monitored and, if necessary, clinical parameters (blood pressure, hematocrit, oxygenation) were adjusted in response to neuromonitoring signals. This analysis is focused on the neurological outcome (paraplegia, stroke) after the use of intraoperative neuromonitoring. Results: Thirty‐day mortality was 10 (12.8%). All patients with continuously stable signals or signals that returned after signal loss developed no spinal cord injury, whereas two out of six of the evaluable patients with signal loss (without return) during the procedure suffered from postoperative paraplegia (one transient and one permanent). Sensitivity and specificity of use of MEP and SSEP were 100% and 94.20% regarding paraplegia, respectively. Conclusions: (1) Preservation of signals or return of signals is an excellent prognostic indicator for spinal cord function. (2) Intraoperative modifications in direct response to the signal change may have averted permanent paralysis in the patients with signal loss without neurologic injury. We have found MEP and SSEP neuromonitoring to be instrumental in the prevention of paraplegia. doi: 10.1111/jocs.12739 (J Card Surg 2016;31:383–389)